ENGLISH LEARNERS’ STRATEGIES IN LEARNING SPEAKING SKILL (A STUDY OF UNDERGRADUATE STUDENT OF ENGLISH EDUCATION STUDY PROGRM AT UNIVERSITAS BENGKULU IN 2016/2017 ACADEMIC YEAR) - Venti Septika Trialoka; Hilda Puspita; Syafrizal Sabarudin (Universitas Bengkulu, 2017)
The aim of this research was to find out the strategies used by the English Education Study Program students in learning speaking skill. It was designed as a descriptive quantitative research. The population was 240 students of English Education Study Program of Universitas Bengkulu in the 2016/2017academic year. The samples were 60 students, taken from 25% of the total population. The data were collected by using a set of questionnai re. There were 30 statements of speaking learning strategies which consisted of three categories of learning strategies proposed by O’Malley and Chamot (1990). They were metacognitive strategy, cognitive strategy, and social affective strategy.The instrument of this research was adapted from Liao and Chiang (2004).The result of this study showed students of English Education Study Program preferred to use all category of that learning strategy. In addition, the most frequently used strategy group by the students was social affective strategy (M=2.67).